2015
DOI: 10.1103/physrevb.92.014405
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiospin-flip conductance of hydrogenated graphene nanoribbons: Spin-orbit interaction and scattering with local impurity spins

Abstract: We calculate the spin-dependent zero-bias conductance G σσ in armchair graphene nanoribbons with hydrogen adsorbates employing a DFT-based ab initio transport formalism including spin-orbit interaction. We find that the spin-flip conductance G σσ can reach the same order of magnitude as the spin-conserving one, G σσ , due to exchange-mediated spin scattering. In contrast, the genuine spin-orbit interaction appears to play a secondary role, only.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 88 publications
1
47
0
Order By: Relevance
“…[15][16][17][18][19][20][21] This vast discrepancy can be reliably explained assuming a small amount (orders of ppm) of resonant magnetic scatters [22][23][24] like for example hydrogen atoms 25,26 or vacancies. 26,27 Related theoretical studies [28][29][30] confirmed that magnetic moments, indeed, strongly affect spin dynamics and can cause the ultra-fast spin relaxation. A recent experiment of the Valenzuela group [31], analyzing graphene's spin-lifetime anisotropy, supports that view and convincingly rules out SOC as a determining factor of the fast spin relaxation.…”
Section: Introductionmentioning
confidence: 95%
“…[15][16][17][18][19][20][21] This vast discrepancy can be reliably explained assuming a small amount (orders of ppm) of resonant magnetic scatters [22][23][24] like for example hydrogen atoms 25,26 or vacancies. 26,27 Related theoretical studies [28][29][30] confirmed that magnetic moments, indeed, strongly affect spin dynamics and can cause the ultra-fast spin relaxation. A recent experiment of the Valenzuela group [31], analyzing graphene's spin-lifetime anisotropy, supports that view and convincingly rules out SOC as a determining factor of the fast spin relaxation.…”
Section: Introductionmentioning
confidence: 95%
“…One way to enhance these interactions is by functionalizing graphene with adatoms and admolecules, which works well for both exchange [2][3][4][5][6][7] and spin-orbit [7][8][9][10][11][12][13][14][15][16] couplings. Functionalized graphene has local "hot spots" of giant exchange and spin-orbit fields, which can be used to investigate spin transport [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This is important since CVD-grown graphene contains extended edgelike defects in the form of grain boundaries [25][26][27][28], unlike bottom-up approaches which may allow the synthesis of more precise geometries [29]. We are further motivated by the strong dependence of GNR transport on edge geometry and impurity distribution [30][31][32][33][34][35][36][37][38][39][40][41][42][43] and by sublattice dependent features in carbon nanotubes [44,45]. We consider both armchair-(AGNR) and zigzag-(ZGNR) edged ribbons, noting the in-built sublattice asymmetry of ZGNRs due to sites along one edge belonging to one sublattice.…”
Section: Introductionmentioning
confidence: 99%